Versatility of Preprotein Transfer from the Cytosol to Mitochondria. Issue 7 (July 2019) - Becker, Thomas; Song, Jiyao; Pfanner, Nikolaus
Abstract : Mitochondrial biogenesis requires the import of a large number of precursor proteins from the cytosol. Although specific membrane-bound preprotein translocases have been characterized in detail, it was assumed that protein transfer from the cytosol to mitochondria mainly involved unselective binding to molecular chaperones. Recent findings suggest an unexpected versatility of protein transfer to mitochondria. Cytosolic factors have been identified that bind to selected subsets of preproteins and guide them to mitochondrial receptors in a post-translational manner. Cotranslational import processes are emerging. Mechanisms for crosstalk between protein targeting to mitochondria and other cell organelles, in particular the endoplasmic reticulum (ER) and peroxisomes, have been uncovered. We discuss how a network of cytosolic machineries and targeting pathways promote and regulate preprotein transfer into mitochondria. Highlights: The majority of mitochondrial proteins are targeted to mitochondria upon the completion of protein synthesis at cytosolic ribosomes (post-translational translocation). A network of chaperones, cochaperones, and further cytosolic factors guides preproteins to the translocase of the mitochondrial outer membrane. Cochaperones such as J-proteins provide selectivity for subgroups of mitochondrial preproteins and bind to specific receptors on the mitochondrial surface. mRNAs and cytosolic ribosomes can associate with the mitochondrial outer membrane. Several mitochondrial proteins are imported in a cotranslational manner via association of ribosome–nascent chain complexes with the translocase of the outer membrane. The targeting pathways of some preproteins to mitochondria, ER, and peroxisomes are in functional crosstalk and can share cytosolic factors. The regulation of cytosolic factors and targeting pathways provides a means of adapting organelle biogenesis to metabolism and environmental cues.